A comparison of bilateral vs. unilateral-biased strength and power training interventions on measures of physical performance in elite youth soccer players - Stern, D.; Gonzalo-Skok, O.; Loturco, I.; Turner, A.; Bishop, C. (The Journal of Strength and Conditioning Research, 2020)
The aim of the present study was to compare the effects of bilateral and unilateral-biased strength and power training programs on measures of physical performance in male youth soccer players. Twenty-three elite youth players (age: 17.6 ± 1.2 years) were randomly assigned to either a unilateral (n = 11) or a bilateral (n = 12) group, who completed a strength and power intervention, twice per week for 6 weeks. The unilateral group completed rear foot elevated split squats (RFESS), single-leg countermovement jumps (SLCMJs), single-leg drop jumps (SLDJs), and single-leg broad jumps (SLBJs). The bilateral group intervention performed back squats, CMJs, drop jumps (DJ), and broad jumps (BJ). A 2 × 2 repeated measures analysis of variance showed no between-group differences. However, within-group differences were evident. The bilateral training group showed significant (p < 0.05) improvements in back squat strength (d = 1.27; %Delta = 26.01), RFESS strength (d = 1.64; %Delta = 23.34), BJ (d = 0.76; %Delta = 5.12), 10-m (d = -1.17; %Delta = 4.29), and 30-m (d = -0.88; %Delta = 2.10) performance. The unilateral group showed significant (p < 0.05) improvements in RFESS strength (d = 1.40; %Delta = 33.29), SLCMJ on the left leg (d = 0.76; %Delta = 9.84), SLBJ on the left leg (d = 0.97; %Delta = 6.50), 10 m (d = -1.50; %Delta = 5.20), and 505 on the right leg (d = -0.78; %Delta = 2.80). Standardized mean differences showed that bilateral training favored improvements in back squat strength and unilateral training favored improvements in RFESS strength, SLDJ on the right leg and 505 on the right leg. These results show that although both training interventions demonstrated trivial-to-large improvements in physical performance, the notion of training specificity was evident with unilateral training showing greater improvements in unilateral test measures.